2012
DOI: 10.1111/j.1365-3024.2012.01365.x
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Leishmania infantum chagasi proteins in urine of patients with visceral leishmaniasis: a promising antigen discovery approach of vaccine candidates

Abstract: Summary Visceral leishmaniasis (VL) is a serious lethal parasitic disease caused by Leishmania donovani in Asia and by Leishmania infantum chagasi in southern Europe and South America. VL is endemic in 47 countries with an annual incidence estimated to be 500 000 cases. This high incidence is due in part to the lack of an efficacious vaccine. Here, we introduce an innovative approach to directly identify parasite vaccine candidate antigens that are abundantly produced in vivo in humans with VL. We combined RP‐… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 64 publications
0
17
0
Order By: Relevance
“…In our former studies in mice we vaccinated the animals with Li-ntf2 formulated with the adjuvant Bp MPLA-SE and showed that this formulation induced IgG2a antibody response and production of IFN-γ by Li-ntf2 specific T cells thus a Th1 biased response [18]. To confirm that this immunization protocol was also effective in dogs, two groups of six month old, male Beagles were immunized three times (one month apart) with either Li-ntf2 mixed with Bp MPLA-SE or with Li-ntf2 in saline.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…In our former studies in mice we vaccinated the animals with Li-ntf2 formulated with the adjuvant Bp MPLA-SE and showed that this formulation induced IgG2a antibody response and production of IFN-γ by Li-ntf2 specific T cells thus a Th1 biased response [18]. To confirm that this immunization protocol was also effective in dogs, two groups of six month old, male Beagles were immunized three times (one month apart) with either Li-ntf2 mixed with Bp MPLA-SE or with Li-ntf2 in saline.…”
Section: Resultsmentioning
confidence: 99%
“…Of note, it is important to highlight that despite the reduced MW of Li-ntf2 (13.9 kDa) and consequent limited antigenic epitope repertoire, this molecule induced partial protection in mice [18] and dogs (this study). In contrast, the successful commercially available dog vaccines [14;15;41-50], which induce better protection than Li-ntf2 , are composed of multiple high MW proteins ranging from 40kDa to 100kDa.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations